1983
DOI: 10.1111/j.1749-6632.1983.tb47814.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Toxic Compounds in Mammalian Cell Cultures

Abstract: The cytotoxic concentrations of about 100 randomly selected drugs and chemicals, tested on HeLa cells in the MIT-24 system and/or in primary cultures of fetal chicken cells, were compared with the lethal doses and/or concentrations of the agents in the mouse and in man. Most agents (80%) had a similar toxicity in vitro and in vivo, suggesting a lethal interference in man with basal functions common to all specialized human tissues as well as cultured cells, i.e., basal cytotoxicity. This high frequency of basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(51 citation statements)
references
References 29 publications
3
45
0
3
Order By: Relevance
“…The dose-response curves of three compounds − acetaminophen, cyclophosphamide and diclofenac sodium − are presented in Fig.1-3. According to IC 50 values in Table 1, the compounds of acetaminophen, cyclophosphamide, diclofenac sodium and disulfiram displayed IC 50 values 2 to 13 times higher in the three cell lines than those in rat primary Almost all of the compounds tested exhibited a rough similarity (differences were generally less than threefold) of IC 50 values in the four cell cultures, which indicates a "basal cytotoxicity" as proposed by Ekwall (1983). It was suggested that for most chemicals, toxicity is a consequence of non-specific alterations in cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…The dose-response curves of three compounds − acetaminophen, cyclophosphamide and diclofenac sodium − are presented in Fig.1-3. According to IC 50 values in Table 1, the compounds of acetaminophen, cyclophosphamide, diclofenac sodium and disulfiram displayed IC 50 values 2 to 13 times higher in the three cell lines than those in rat primary Almost all of the compounds tested exhibited a rough similarity (differences were generally less than threefold) of IC 50 values in the four cell cultures, which indicates a "basal cytotoxicity" as proposed by Ekwall (1983). It was suggested that for most chemicals, toxicity is a consequence of non-specific alterations in cellular functions.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Cytotoxicity Cytotoxicity is defined as the negative consequences resulting from disturbance with structures and/or processes required for cell survival, proliferation, and function. [19] This causes cell necrosis (disintegration of membrane integrity) and lysis. The cells may decrease in viability by ceasing growth and dividing or even trigger apoptosis (death of program cell).…”
Section: Fecal Watermentioning
confidence: 99%
“…No animal testing was performed for this study. Following the method described by Evans et al (2001), the lowest LD 50 value of a test chemical that 2) MEIC; Multicentre Evaluation of In Vitro Cytotoxicity (Ekwall et al 1983). …”
Section: Ld 50 Valuesmentioning
confidence: 99%